Pendekatan Mimesis untuk Keberlanjutan Arsitektur Vernakular - Anna Lucy Rahmawati; Lilianny Sigit Arifin; Yohanes Basuki Dwisusanto (CV. Gio Architect, 2023)
This paper presents an outline of the literature review and is part of a dissertation research proposal that puts forward a mimetic approach in relation to the preservation efforts for the sustainability of vernacular architecture. The topic put forward is motivated by the discourse of extinction of vernacular architecture and preservation efforts undertaken to maintain and/or maintain its sustainability. The phenomenon of imitation is then presented to show the relationship between the act of imitating with the trace of the sustainability of vernacular architecture. From this phenomenon, it is assumed that the act of imitating as part of a broad concept of mimesis, might be able to offer a new method that is effective and can be used to fill research gaps related to the issue of sustainability of vernacular architecture. This assumption is a motivation to conduct a literature review using an integrative approach to build a theoretical foundation that can produce novelty from planned research. The result of this literature review is a mimetic trilogy diagram, as an approach tool for the sustainability of vernacular architecture.